Evaluation of Master of Education Program in Educational Administration (Revised Curriculum 2562 B.E.), Nakornrachasima College - nakvichet, krongrip; Lunsomrong, Patruthai; Wongwatkasem, Wiralphat; Thongsuddhi, Vipas; Watanasak, Krisda; Meengen, Boonlue (Journal for Developing the Social and Community, 2023)
The purposes of this study were 1) to evaluate the Master of Education Program in Educational Administration.(Revised Curriculum 2562 B.E.), Nakornrachasima College. 2) to study the suggestion of the stakeholders for the Master of Education Program in Educational Administration.(Revised Curriculum 2562 B.E.), Nakornrachasima Collegedevelopment. The study was comprised 4 factors context, input, process and product. To fulfill the objectives a questionnaire was applied for collecting data consisted of 79 students,14 fulltime lecturers, 17 lecturers and 64 graduate users. The results of study were as follows: 1) The evaluation results of the the Master of Education Program in Educational Administration.(Revised Curriculum 2562 B.E.), Nakornrachasima College : (1) The contexts were at very high suitable level ; objectives and subjects of curriculum were correspondent to all national, college and faculty’s vision and also correspondent to the graduate users’ need. (2) The input were at very high suitable level ; learner feature, lecturers’ skill and attribute, educational planning. (3) The process were at very high suitable level ; curriculum administration, education resource management and learning and evaluating. (4) The product were at very high suitable level ; graduate’s characteristic including administrating and leadership. 2) The suggestion for the Master of Education Program in Educational Administration.(Revised Curriculum 2562 B.E.), Nakornrachasima College were should be (1) change the goal, vision and the mission correspondent to new national education policy; add new universality subject matters. (2) manage degree and experience transferring for new student. (3) manage student activities organizing with focusing on virtual condition, technology development, manage the lecturer development and collaboration. (4) focus on innovative graduate with abilities of using technology and creating network for their school administration.